Identification of lncRNA‐155 encoded by MIR155HG as a novel regulator of innate immunity against influenza A virus infection. (29th May 2019) - Maarouf, Mohamed; Chen, Biao; Chen, Yuhai; Wang, Xuefei; Rai, Kul Raj; Zhao, Zhonghui; Liu, Shasha; Li, Yingying; Xiao, Meng; Chen, Ji‐Long
Abstract: Long noncoding RNAs (lncRNAs) are single‐stranded RNA molecules longer than 200 nt that regulate many cellular processes. MicroRNA 155 host gene (MIR155HG) encodes the microRNA (miR)‐155 that regulates various signalling pathways of innate and adaptive immune responses against viral infections. MIR155HG also encodes a lncRNA that we call lncRNA‐155. Here, we observed that expression of lncRNA‐155 was markedly upregulated during influenza A virus (IAV) infection both in vitro (several cell lines) and in vivo (mouse model). Interestingly, robust expression of lncRNA‐155 was also induced by infections with several other viruses. Disruption of lncRNA‐155 expression in A549 cells diminished the antiviral innate immunity against IAV. Furthermore, knockout of lncRNA‐155 in mice significantly increased IAV replication and virulence in the animals. In contrast, overexpression of lncRNA‐155 in human cells suppressed IAV replication, suggesting that lncRNA‐155 is involved in host antiviral innate immunity induced by IAV infection. Moreover, we found that lncRNA‐155 had a profound effect on expression of protein tyrosine phosphatase 1B (PTP1B) during the infection with IAV. Inhibition of PTP1B by lncRNA‐155 resulted in higher production of interferon‐beta (IFN‐β) and several critical interferon‐stimulated genes (ISGs). Together, these observations reveal that MIR155HG derived lncRNA‐155 can be induced by IAV, which modulates host innate immunity during the virus infection via regulation of PTP1B‐mediated interferon response.